2022
DOI: 10.1111/epi.17467
|View full text |Cite
|
Sign up to set email alerts
|

Responsive neurostimulation with low‐frequency stimulation

Abstract: Deep brain stimulation and responsive neurostimulation (RNS) use highfrequency stimulation (HFS) per the pivotal trials and manufacturerrecommended therapy protocols. However, not all patients respond to HFS. In this retrospective case series, 10 patients implanted with the RNS System were programmed with low-frequency stimulation (LFS) to treat their seizures; nine of these patients were previously treated with HFS (100 Hz or greater). LFS was defined as frequency < 10 Hz. Burst duration was increased to at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Programming approaches are largely determined by parameters used in pivotal trials, in which high-frequency (>100 Hz) stimulation has typically been used for invasive modalities [42 ▪ ]. However, low-frequency stimulation (<10 Hz) has been used for continuous neocortical stimulation [4], DBS-CM [43] and RNS [44 ▪ ]. Stimulation frequency may affect limbic system deactivation [45] and seizure clustering [46 ▪ ].…”
Section: Emerging Approaches and Usesmentioning
confidence: 99%
“…Programming approaches are largely determined by parameters used in pivotal trials, in which high-frequency (>100 Hz) stimulation has typically been used for invasive modalities [42 ▪ ]. However, low-frequency stimulation (<10 Hz) has been used for continuous neocortical stimulation [4], DBS-CM [43] and RNS [44 ▪ ]. Stimulation frequency may affect limbic system deactivation [45] and seizure clustering [46 ▪ ].…”
Section: Emerging Approaches and Usesmentioning
confidence: 99%
“…[46][47][48] Many unanswered questions surround candidate and stimulation parameter selection. For example, in a study among 10 patients with poor response to high-frequency stimulation, transition to low-frequency stimulation was associated with a 76% median seizure reduction compared to pre-implantation baseline, 49 raising questions about how to tailor parameters. Moreover, future investigation should not just focus on optimizing stimulation parameters, but also on how short-term biomarker changes might predict long-term clinical response, and how to tailor stimulation timing to an individual patient's high-risk periods per RNS electrocorticography.…”
Section: Neurostimulationmentioning
confidence: 99%
“…98 Despite these differences, interestingly, outcomes are generally similar across a wide range of stimulation approaches. 99 Certainly, stimulation parameters and details of brain state dynamics can affect outcomes, and yet sometimes even basic, standardized approaches are similarly effective.…”
Section: Stimulation Parameters To Dynamotypes In a Dynamic Systems F...mentioning
confidence: 99%
“…In one example, stimulation of the medial septum in a rat hippocampal kindling model showed that responsive closed loop stimulation at the level of individual stimulation pulses (which is not the case with RNS) was effective, whereas open loop stimulation was not 98 . Despite these differences, interestingly, outcomes are generally similar across a wide range of stimulation approaches 99 . Certainly, stimulation parameters and details of brain state dynamics can affect outcomes, and yet sometimes even basic, standardized approaches are similarly effective.…”
Section: Adjustment Of Stimulation Parameters To Dynamotypes In a Dyn...mentioning
confidence: 99%